Penggunaan Model Pembelajaran Kooperatif Jigsaw Untuk Meningkatkan Hasil Belajar Matematika Pada Siswa Kelas XII SMA Negeri 8 Pandeglang - Endan Muldani (Universitas Mathla'ul Anwar Banten, 2020)
Mathematics learning outcomes of SMA Negeri 8 Pandeglang students are still low compared to other subjects. The low learning outcomes of students of SMA Negeri 8 Pandeglang are caused by many factors, including: 1) some students still think mathematics is a difficult and boring subject; 2) students are less active and creative in learning; 3) teachers are less varied in using conventional approaches. One effort to overcome these problems in this study the authors use a Jigsaw cooperative learning model. This research was conducted at SMA Negeri 8 Pandeglang, conducted in August 2017 to September 2017. The type of this research was Classroom Action Research (CAR). Based on the results of this study indicate that the use of Jigsaw learning models on the material Dimension Three student learning outcomes increase. It was shown the average value of the class from 44.86 in daily tests KD 3.1 to 71.09 in the first cycle and the average value to 76.41 in the second cycle. This is indicated by the value of mastery learning KD 3.1 of 34.34% increased to 46.88% in the first cycle and to be 68.75% in the second cycle. Based on data analysis and discussion of research results, the authors conclude that the use of Jigsaw's cooperative learning model can improve mathematics learning outcomes in basic competencies mendeskripsikan jarak dalam ruang (antar titik, titik ke garis, dan titik ke bidang). Keywords : Learning Outcomes, Cooperative Learning, Jigsaw